2017
DOI: 10.1177/2047173416688039
|View full text |Cite
|
Sign up to set email alerts
|

Civic Education policies: Their effect on university students’ spirit of nationalism and patriotism

Abstract: This study aims to describe the effect of implementing Civic Education policies in a university on the development of students’ sense of nationalism and patriotism; this is analysed from the perspective of Edward III’s public policy implementation dimension and employs a quantitative approach based on the descriptive verification method. The findings show that the implementation of Civic Education policies at a university influences students’ sense of nationalism and patriotism. The degree of influence is low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…This is also reflected in the implementation of Pancasila educational learning that is closely related to citizenship education when introducing citizenship values such as nationalism and patriotism. Consistent with the statement that ... "The implementation of civic education policies at a university has some effect on students' sense of nationalism and patriotism by students [9].…”
Section: Theoretical Reviewmentioning
confidence: 58%
See 1 more Smart Citation
“…This is also reflected in the implementation of Pancasila educational learning that is closely related to citizenship education when introducing citizenship values such as nationalism and patriotism. Consistent with the statement that ... "The implementation of civic education policies at a university has some effect on students' sense of nationalism and patriotism by students [9].…”
Section: Theoretical Reviewmentioning
confidence: 58%
“…The planting of Spiritual values and Unpar Basic Values (SINDU) is also carried out in national seminars and school activities as a form of excavation of the Indonesian nation's culture that is based on the values of God Almighty to improve human relations with God, humans and fellow human beings and is carried out in concert with efforts the improvement of student nationalism at universities as a characteristic of the relationship with the science of Civic Education and its policy, Civic Education policy implementation at a university has some effect on students' sens of nationalism and patriotism [28].…”
Section: Resultsmentioning
confidence: 99%
“…To support this success, Muttaqin and Raharjo (2018) explained that school requires to establish cooperation among parents and make the teacher role model for students. In this case, the teachers' role is huge because teachers have a suitable competency that will determine the instilling of values toward students (Nurdin, 2017). Habituated activities through school culture are formed in routine activities, occur spontaneously, conditional, the exemplary for school residents.…”
Section: Discussionmentioning
confidence: 99%
“…This component of citizenship knowledge embodied in the form of five important questions that must be continuously submitted as a learning resource for Citizenship Education [27]. The five questions in question are (1) what is the life of citizenship, politics and government; (2) what are the basics of the political system; (3) how government is formed by the constitution; (4) how is the relationship between a country and another country; (5) what is the role of citizens in government.…”
Section: A Civic Knowledgementioning
confidence: 99%
“…There is a research about civic education policy in university, showed the findings that the implementation of the policy on Citizenship Education at the university influenced the sense of nationalism and student patriotism. The level of influence is low because of several important factors, which include the following: (1) the development of Citizenship Education material delegated to each university or to lecturers who teach Citizenship Education subjects; thus, materials do not consistently focus on content related to patriotism and nationalism and (2) policies are implemented ineffectively in the dimensions of (a) communication, because they are not ideally communicated; (b) resources, because lecturers have a variety of competencies without a consistent academic background; (c) disposition, because the executor lacks commitment because the number of educators is limited compared to the number of students; and (d) bureaucratic structure, because this varies according to the university, resulting in the failure of command unity and bureaucratic fragmentation [2].…”
Section: Introductionmentioning
confidence: 99%